Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3390/cancers14020442
|View full text |Cite
|
Sign up to set email alerts
|

Keep Calm and Carry on with Extra Centrosomes

Abstract: Aberrations in the centrosome number and structure can readily be detected at all stages of tumor progression and are considered hallmarks of cancer. Centrosome anomalies are closely linked to chromosome instability and, therefore, are proposed to be one of the driving events of tumor formation and progression. This concept, first posited by Boveri over 100 years ago, has been an area of interest to cancer researchers. We have now begun to understand the processes by which these numerical and structural anomal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 257 publications
(337 reference statements)
0
11
0
Order By: Relevance
“…Previously, to our knowledge, maturation of amplified centrioles via PLK4 induction was depicted through illustrations which suggested that separate CRs were generated without any functional linkage between amplified centrosomes [16, 27]. In our proposed model (Fig 1H), we suggest that PLK4 induced CRCs should be linked to each other with centrosomal linker proteins until separation in prophase.…”
Section: Resultsmentioning
confidence: 58%
“…Previously, to our knowledge, maturation of amplified centrioles via PLK4 induction was depicted through illustrations which suggested that separate CRs were generated without any functional linkage between amplified centrosomes [16, 27]. In our proposed model (Fig 1H), we suggest that PLK4 induced CRCs should be linked to each other with centrosomal linker proteins until separation in prophase.…”
Section: Resultsmentioning
confidence: 58%
“…For instance, cancer cells have found a way to deal with multiple centrosomes and still assemble a bipolar spindle even with more than two centrosomes. The mechanism named centrosome clustering consists by being able to form a bipolar spindle with one centrosome at one pole and three clustered centrosomes at the other pole [ 87 ]. Even if the mechanism is not fully understood, an inhibition of the clustering mechanism has been shown to be effective in eliminating cancer cells that have developed this strategy to proliferate in the presence of supernumerary centrosomes [ 88 ].…”
Section: Discussionmentioning
confidence: 99%
“…36 Cells with extra centrosomes undergoing bipolar division can sustain aneuploidy by merotelic attachments causing lagging chromosomes. 8,37 Still, the generation of aneuploidy at cell division does not necessarily mean that we obtain surviving cells with clonal chromosome alterations, since the aneuploid cell have to go into the cell cycle again and be allowed to pass through it, that is, a certain tolerance to aneuploidy is needed. It has previously been shown that defective TP53 affects the function of homologous recombination repair and nonhomologous end joining.…”
Section: Discussionmentioning
confidence: 99%
“…In cells with intact p53 function, multipolar cell division is often avoided by clustering of extra centrosomes 36 . Cells with extra centrosomes undergoing bipolar division can sustain aneuploidy by merotelic attachments causing lagging chromosomes 8,37 . Still, the generation of aneuploidy at cell division does not necessarily mean that we obtain surviving cells with clonal chromosome alterations, since the aneuploid cell have to go into the cell cycle again and be allowed to pass through it, that is, a certain tolerance to aneuploidy is needed.…”
Section: Discussionmentioning
confidence: 99%